Interpreting African American history and culture at museums and historic sites - Balgooy, Max van (Interpreting history., 2014)
This diverse anthology addresses both historical research and interpretive methodologies, including investigating church and legal records, using social media, navigating sensitive or difficult topics, preserving historic places, engaging students and communities, and strengthening connections between local and national history.